Numerical investigations of Re-independence and influence of wall heating on flow characteristics and ventilation in full-scale 2D street canyons. (February 2021) - Yang, Hongyu; Lam, Cho Kwong Charlie; Lin, Yuanyuan; Chen, Lan; Mattsson, Magnus; Sandberg, Mats; Hayati, Abolfazl; Claesson, Leif; Hang, Jian
Abstract: Validated by wind tunnel data, this study numerically investigates the integrated impacts of wind and thermal buoyancy on urban turbulence, ventilation and pollutant dispersion in full-scale 2D deep street canyons (aspect ratio AR  =  H/W  = 3 and 5, W  = 24 m). Isothermal urban airflows for such deep street canyons can be Reynolds-number-independent when reference Reynolds number ( Re ) exceeds the critical Re ( Re c ~10 6, 10 7 when AR  = 3, 5), i.e. AR  = 5 experiences two main vortices and one-order smaller NEV * (~10 −3, the normalized net escape velocity) than AR  = 3 with a single main vortex ( NEV *~10 −2 ). With sufficiently large Re ( Re  >  Re c ) and the same air-wall temperature difference ( Ri  = 2.62, 4.36 when AR  = 3, 5), four uniform wall heating patterns were considered, including leeward-wall heating (L-H), windward-wall heating (W–H), ground heating (G-H), and all-wall heating (A-H). Various indicators were adopted to evaluate street ventilation and pollutant dilution capacity (e.g. age of air ( τ, s), NEV *, pollutant transport rates ( PTR )). Full-scale wall heating produces a strong upward near-wall buoyancy force, which significantly influences flow patterns and improves street ventilation for most cases. When AR  = 3, L-H strengthens the single-vortex airflow. When AR  = 5, L-H converts the isothermal double vortices into a single-clockwise vortex. For both AR s, W–H reverses the main clockwise vortex to an enhanced counterclockwise one, moreover G-H and A-H cause a more complicated multi-vortex pattern than isothermal cases. Overall, when AR  = 3, L-H and W–H increase NEV * by 68% and 40% than the isothermal case. When AR  = 5, four wall heating patterns all raise NEV * considerably (by 150%–556%). For both AR s, the L-H, W–H and A-H amplify the contribution of mean flows on removing pollutants but reduce that by turbulent diffusion compared with isothermal cases. Graphical abstract: Image 1 Highlights: We use CFD to study how wall heating affects ventilation in deep street as Ri ~2, 4. 2D canyon flow is Re -independent as Re exceeds Re c (~10 6, ~10 7 as H/W  = 3, 5). Leeward, windward, ground and all wall heating greatly alter street flow pattern. Ventilation improves with lateral wall heating as AR  = 3 and all four types as AR  = 5. Lateral/all-wall heating raise contribution of mean flows on pollutant removal.